A CD-romance: CTA's CD-ROM project for the ACP States - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The spectacular progress in information technology in recent decades has not always reached Third World countries which need access to scientific and technical information (STI) which is vital to their agricultural and rural development. The use of...